(untitled) (KASBIT Business Journal, 2022)
The purpose of this research is to determine the impact of venture financing on entrepreneurship. This research will assist in bridging the gap between the entrepreneurs who have established their business not more than five years ago & the upcoming entrepreneurs who want to utilize venture financing in establishing their business. For this purpose, the survey method has been opted & data has been gathered from 40 entrepreneurs. Entrepreneurs responded regarding different aspects of the business to determine the present, past & future growth of entrepreneurial Activities to determine how appropriately venture financing could be utilized &, based on their experiences, how newbies can establish their business more effectively. The research is based wholly on the considerations & priorities of entrepreneurs for their business.